A coaxial-output rolled strip pulse forming line based on multi-layer films. (24th January 2018) - Su, Jian-Cang; Li, Rui; Cheng, Jie; Yu, Bin-Xiong; Zhang, Xi-Bo; Zhao, Liang; Huang, Wen-Hua
Abstract: A coaxial-output rolled strip pulse-forming line (RSPFL) with a dry structure is researched for the purpose of miniaturization and all-solid state of pulse-forming lines (PFL). The coaxial-output RSPFL consists of a coaxial-output electrode (COE) and a rolled strip line (RSL). The COE is characterized by quasi-coaxial structure, making the output pulse propagate along the axial direction with a small output inductance. The RSL is rolled on the COE, whose transmission characteristics are analyzed theoretically. It shows that the RSL can be regarded as a planar strip line when the rolling radius of the strip line is larger than 60 times of the thickness of the insulation dielectric layer of RSL. CST modeling was carried out to simulate the discharging characteristic of the coaxial-output RSPFL. It shows that the coaxial-output RSPFL can deliver a discharging pulse with a rise time <6 ns when the impedance of the RSL matches that of the COE, which confirms the theoretical analysis. A prototype of the coaxial-output RSPFL was developed. A 49-kV discharging pulse on a matched load was achieved when it was charged to 100 kV. The discharging waveform has a pulse width of 32 ns, with a rise time of 6 ns, which is consistent with the simulation waveform. An energy-storage density of 1.9 J/L was realized in the coaxial-output RSPFL. By the method of multi-stage connection in series, a much higher output voltage is convenient to be obtained.